2023
DOI: 10.3390/healthcare11020248
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients during COVID-19 Pandemic: A Mini-Review

Abstract: Since its emergence, coronavirus disease 2019 (COVID-19) has affected the entire world and all commerce and industries, including healthcare systems. COVID-19 adversely affects cancer patients because they are immunocompromised. Increased COVID-19 infection and shortage of medical supplies, beds and healthcare workers in hospitals affect cancer care. This paper includes a description of the existing research that shows the impact of COVID-19 on the management of cancer patients. Aged people with various chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…An association between worse outcomes among cancer patients was observed during the first period and this is consistent with published literature showing that COVID-19 is more severe in cancer patients. Additionally, previous studies have shown that hematologic cancer patients and subjects with lung cancer experience more severe COVID-19 ( 28 , 29 ). In our study, we observed a worsened outcome in subjects with both hematologic and solid cancers, as well as in patients undergoing chemotherapy, and there was no difference between the two groups in terms of outcome (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…An association between worse outcomes among cancer patients was observed during the first period and this is consistent with published literature showing that COVID-19 is more severe in cancer patients. Additionally, previous studies have shown that hematologic cancer patients and subjects with lung cancer experience more severe COVID-19 ( 28 , 29 ). In our study, we observed a worsened outcome in subjects with both hematologic and solid cancers, as well as in patients undergoing chemotherapy, and there was no difference between the two groups in terms of outcome (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 pandemic has mainly affected the most vulnerable patients, such as patients with cancers or chronic diseases, as well as those who require ready access to healthcare services due to acute life-threatening conditions [ 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed a substantial impact of the COVID-19 pandemic on cancer care (Linjawi et al 2023 ). Depending on the geography and study design, varying degrees of delays and cancellations of cancer treatment, screening and diagnosis have been observed, leaving the medium- and long-term impact on cancer care uncertain (Muka et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%